Exclusive Data, Price Manipulation and Market Leadership - Yiquan Gu; Leonardo Madio; Carlo Reggiani (Center for Economic Studies and ifo Institute (CESifo), 2019)
The unprecedented access of firms to consumer level data not only facilitates more precisely targeted individual pricing but also alters firms' strategic incentives. We show that exclusive access to a list of consumers can provide incentives for a firm to endogenously assume the price leader's role, and so to strategically manipulate its rival's price. Prices and profits are non-monotonic in the length of the consumer list. For an intermediate size, price leadership entails a semi-collusive outcome, characterized by supra-competitive prices and low consumer surplus. In contrast, for short or long lists of consumers, exclusive data availability intensifies market competition.
Keywords: D43; K21; L11; L13; L41; L86; M21; M31; 330; exclusive data; price leadership; personalized pricing; price discrimination